DIALEKTIKA FUNGSIONAL ANTARA HUKUM DAN OTORITAS KEKUASAAN NEGARA - Arif Hidayat (Masalah-Masalah Hukum, 2013)
This study aimed to describe the functional dialectic between Jaw and power authorities. The result: (1) the authoricy is a conception of social relations between the two parties or two institutions that are each influences, dominating or exploitative; (2) legal characteristics can be viewed from the authorities that form, and substance of the work in organizing the community; (3) functional dialectic between Jaw and state power authorities gave birth to two patterns of relationships, which is identical to the rule of Jaw and vice versa. Finally, the 'state' as a sovereign authority through the institutionalization of formal institutions should be able to put laws autonomous in accordance with the principles of human rights, in order to avoid 'trade off between the rule of law.